Comparison of trace mineral repletion strategies in feedlot steers to overcome diets containing high concentrations of sulfur and molybdenum - Hartman, Sarah J (J Anim Sci, 2018)
To compare trace mineral (TM) repletion in feedlot steers after depletion by S and Mo, 72 Red Angus steers blocked by BW (253 ± 14 kg) were assigned (6 steers per pen, fed via GrowSafe bunks) to corn silage depletion diets (depletion, DEP) supplemented with NRC (1996) recommended concentrations of Cu, Mn, Se, and Zn (CON) or supplemented with 0.3% S (CaSO(4)), 2 mg of Mo/kg dry matter (DM), and no added Cu, Mn, Zn, or Se (antagonist, ANT). Three 62 d TM repletion strategies (repletion, REP) were applied within DEP diets on day 89: 1) Multimin90 injection (contains Cu, Mn, Se, Zn) and 100% of recommended Cu, Mn, Zn, and Se from inorganic sources (ITM), 2) saline injection and 150% of recommended TM from inorganic sources (ING), or 3) saline injection and 150% of recommended TM provided as 25% organic and 75% inorganic sources (BLEND). Subcutaneous injections were given at 1 mL/68 kg BW. Inorganic sources were Cu, Mn, and Zn SO(4), and sodium selenite, and organic sources were Availa Cu, Mn and Zn, and SelPlex Se. Repletion period liver and blood were collected on day −10, 14, 28, and 42 and data were analyzed as a 2 × 3 factorial (n = 12 steers per treatment) using Proc Glimmix of SAS with plasma and liver analytes analyzed as repeated measures. Liver Cu, Se, and Mn were decreased (P < 0.01) by ANT during DEP. There were no DEP × REP × day interactions in liver TM (P ≥ 0.18). A DEP × day effect was noted for liver Cu (P < 0.01) and Mn (P = 0.07), where ANT Cu increased linearly from day 0 to day 42, CON Cu was slightly increased on day 14 and day 28, and ANT Mn was lesser than CON Mn on all days except day 42. There were REP × day effects on liver Cu (P < 0.01) and Se (P < 0.01) where status was improved by ITM by day 14, increased in BLEND by day 28, and not different by day 42. Liver Se concentrations were lesser (P < 0.01) in ANT vs. CON throughout repletion. Liver Zn was greater (P < 0.01) on day 0 than day 14, 28, and 42, and concentrations were greater on day 42 than day 28. Glutathione peroxidase activity tended to be lesser (P = 0.07) on day 14 relative to other days. Manganese superoxide dismutase activity was lesser (P < 0.01) on day 14 and 28 compared to day 0 and 42, and tended to be lesser (P = 0.06) in ANT than CON during repletion. Final body weight (BW) and average daily gain (ADG) were not affected by treatment (P ≥ 0.60), and ANT decreased dry matter intake (DMI) (P = 0.04) and improved G:F (P < 0.01) during repletion. All repletion strategies were effective at increasing TM status of steers, and ITM had the most rapid recovery of Cu and Se status, followed by BLEND, and ING.